KOMPOSISI KIMIA DAN UJI AKTIVITAS ANTIBAKTERI MINYAK KEMANGI (Ocimum americanum L.) TERHADAP BAKTERI Escherichia coli, Shigella sonnei, DAN Salmonella enteritidis - Asep Kadarohman; Gebi Dwiyanti; Yuni Anggraeni; Lela Lailatul Khumaisah (The East Java Biological Society, 2011)
The chemical composition and antibacterial activity of basil oil (Ocimum americanum L.) against Escherichia coli, Shigella sonnei and Salmonella enteritidis have been determined. Basil oils were isolated from leaves and stems of basil (Ocimum americanum L.) with percolation method and analyzed by FTIR and GC-MS spectrometry. The antibacterial activity of basil oils were obtained by Agar diffusion method with various concentration (v/v) 2, 4, 6, 8, and 10% with ethanol p.a. as negative control, thiamfenicol, and tetracycline 500 mg as positive control. The produces essential oils from leaves and stems of basil by percolation are 1.06 and 0.22%, respectively. There are 22 components of basil oil were identified, with a major component are citral (35.58%) and neral (29.56% ). Basil oil has not effectively against Escherichia coli and Shigella sonnei but effectively against Salmonella enteritidis at concentration 8 and 10%, with inhibition zone diameter are 10.25 and 10.93 mm respectively.